The analytical investigation of the concrete mixture deposition process by the concrete 3d printer extruder - Orysenko, Olexandr; Nesterenko, Mykola; Shokalo, Artem (Academic journal Industrial Machine Building Civil Engineering, 2022)
The construction of buildings using 3D printing is becoming increasingly popular. However, this technology, despite its numerous advantages, also has its drawbacks. To minimize the impact of these drawbacks on the quality of construction work, scientifically substantiated approaches can be applied to improve both the technology itself and the machines used in the process. One of the factors that affect the quality of material deposition on the printing surface is the alignment of the extruder’s productivity of the construction 3D printer with the speed of its movement above the surface. This can be achieved by considering the physicomechanical properties of the concrete mixture and the method of its delivery to the application area. To describe the mixture’s delivery through a narrow channel between the nozzle end of the extruder and the printing surface, the Poiseuille method is proposed, modeling the mixture with the Herschel-Bulkley rheological model. Analytical dependencies have been derived to determine the extruder’s productivity and the speed of the mixture extrusion through the nozzle.